Reading Revelation : a comparison of four interpretive translations of the Apocalypse - Pate, C. Marvin (Grand Rapids, Mich. : Kregel Academic & Professional, 2009)
The mark of the Beast, the Antichrist, the seven seals, the second coming of Christ, the millennium. These intriguing and endlessly contentious ideas and images all come together in the book of Revelation, a rich and hermeneutically complicated Scripture that, unsurprisingly, has no universally accepted interpretation. Instead, the study of Revelation has customarily fallen into four major-and essentially conflicting-hermeneutical approaches: preterist (past), historicist, futurist, and idealist (spiritual). Reading Revelation compares these four major approaches to Revelation by laying out the different interpretive translations provided by each school of thought in parallel columns and-in order to provide a standard of reference-includes a fifth column presenting the Greek text and a literal word-for-word translation.
"The study of Revelation has ... fallen into four major ... hermeneutical approaches: preterist (past), historicist, futurist, and idealist (spiritual). C. Marvin Pate compares these four major approaches by laying out the different interpretive translations provided by each school of thought in parallel columns alongside the Greek text and a literal word-for-word translation."-- Back cover.
Keywords: Bible. Revelation -- Criticism, interpretation, etc; Bible. Revelation